Charged drug delivery by ultrafast exponentially grown weak polyelectrolyte multilayers : amphoteric properties, ultrahigh loading capacity and pH-responsiveness - Yuan, Weiyong (2013)
Exponentially growing layer-by-layer hierarchical nanoporous films have been used as a promising system for controlled drug loading/release applications. However, its growth mechanism and factors affecting the drug loading/release are still unclear. In this study, high molecular weight branched poly(ethyleneimine) (PEI) and poly(acrylic acid) (PAA) were utilized as model weak polyelectrolytes to investigate the growth mechanism and the drug loading/release of the multilayers. The pH-dependent growth behavior, interdiffusion of PEI and morphological changes of the film indicate that a pH-dependent polyelectrolyte interdiffusion mechanism is involved in the ultrafast exponential growth process. It is discovered, for the first time, that the fabricated films possess a pH-triggered switchable polarity and tunable charge density associated to the outermost layer, which can enable the loading of anionic or cationic drugs while offering a broad range of pH-controlled release rates and ultralong release times. The multi-layered film has also achieved the highest pH-controlled drug loading/release capacity. This study not only provides a superior platform for the controlled delivery of charged drugs, but also proposes an exponential growth mechanism for weak polyelectrolyte multilayered films.